Rate of Ascent and Acute Mountain Sickness at High Altitude. Issue 2 (March 2015) - Hsu, Tai-Yi; Weng, Yi-Ming; Chiu, Yu-Hui; Li, Wen-Cheng; Chen, Pang-Yen; Wang, Shih-Hao; Huang, Kuo-Feng; Kao, Wei-Fong; Chiu, Te-Fa; Chen, Jih-Chang
Abstract : Objective: To examine the effect of ascent rate on the induction of acute mountain sickness (AMS) in young adults during a climb to Jiaming Lake (3350 m) in Taiwan. Design: Prospective, nonrandomized. Setting: Climb from 2370 to 3350 m. Participants: Young adults (aged 18 to 26 years) (N = 91) chose to participate in either the fast ascent (3 days; n = 43) or slow ascent (4 days; n = 48) group (1 and 2). Assessment of Risk Factors: Two criteria were used to define AMS. A Lake Louise score ≥3 and Lake Louise criteria [in the setting of a recent gain in altitude, the presence of headache and at least 1 of gastrointestinal discomfort (anorexia, nausea, or vomiting), fatigue or weakness, dizziness or lightheadedness, or difficulty sleeping]. Main Outcome Measures: Heart rate, blood oxygen saturation (SaO2 ), and symptoms of AMS were monitored each morning and evening. Results: Baseline characteristics were similar between groups, except for significant differences in history of alcohol consumption ( P = 0.009) and climbing experience above 3000 m ( P < 0.001). The incidence of AMS was not associated with the rate of ascent. Acute mountain sickness was most prevalent in group 1 on day 2 in the evening and in group 2 on day 3 in the evening. In both groups, AMS correlated with the initial reduction in SaO2 . Body mass index (BMI) >24 kg/m 2 was identified as a significant risk factor for AMS. Conclusions: The development of AMS was closely associated with an initial reduction in SaO2 . A BMI >24 kg/m 2 also contributed to the occurrence of AMS. Clinical Relevance: These findings indicate that factors other than ascent rate should be considered when trying to ameliorate the risk of AMS.